2001
DOI: 10.1046/j.1471-8278.2001.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of simple sequence repeat (SSR) markers for the assessment of gene flow and genetic diversity in pigeonpea (Cajanus cajan)

Abstract: Pigeonpea (Cajanus cajan) is an important subsistence crop in India where traditional landraces and improved hybrids are grown alongside each other. Gene flow may result in genetic erosion of these landraces and their wild relatives, whilst transgene escape from future genetically engineered varieties is another potential hazard. To assess the impact of these factors gene flow needs to be measured. A set of 10 simple sequence repeat markers have been developed, which exhibit polymorphism across a range of pige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 8 publications
14
71
7
Order By: Relevance
“…culinaris) were used for PCR amplification to study transferability as well as their utility in genetic diversity analysis of pigeonpea cultivars. The pigeonpea microsatellite markers were based on the sequences published by Burns et al (2001) whereas common bean and lentil SSR markers were Physiol. Mol.…”
Section: Microsatellite Markers and Pcr Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…culinaris) were used for PCR amplification to study transferability as well as their utility in genetic diversity analysis of pigeonpea cultivars. The pigeonpea microsatellite markers were based on the sequences published by Burns et al (2001) whereas common bean and lentil SSR markers were Physiol. Mol.…”
Section: Microsatellite Markers and Pcr Amplificationmentioning
confidence: 99%
“…Despite its importance in nutritional security, pigeonpea has not benefited much from the advances made in the field of genomic tools and molecular markers (Datta et al, 2009). As compared to large number of markers in common bean (L'taief et al, 2008;Blair et al, 2003), chickpea (Choudhary et al, 2009;Sethy et al, 2006), and lentil (Hamwieh et al, 2009;Hamwieh et al, 2005), only 109 microsatellite markers are reported so far in pigeonpea (Burns et al, 2001;Odeny et al, 2007;Odeny et al, 2009). Therefore, there is an urgent need to increase the number of polymorphic microsatellite markers in pigeonpea for diversity analysis and mapping of important traits.…”
Section: Introductionmentioning
confidence: 99%
“…As genetic diversity in cultivated pigeon pea (C. cajan) is low (Burns et al 2001;Yang et al 2006), linkage maps have not been constructed in intraspecific mapping populations so far. Sufficiently large numbers of common markers are required possibly with good SSRs or some other co-dominant markers to establish synteny/colinearity between these maps in future.…”
Section: Discussionmentioning
confidence: 99%
“…As very few (∼10%) polymorphisms have been identified in cultivated pigeon pea lines using a limited number of SSR and DArT markers (Burns et al 2001;Yang et al 2006), an interspecific mapping population was developed by using pigeon pea (C. cajan) accession ICP 28 and ICPW 94 from a wild relative species of pigeon pea (C. scarabaeoides) to avail maximum polymorphism and to generate the first generation linkage map. Here we demonstrate that DArTs can be effectively applied to genetic linkage mapping of pigeon pea and report the first genetic linkage map of pigeon pea.…”
Section: Introductionmentioning
confidence: 99%
“…Ten SSR primer pairs (Burns et al, 2001) were used for genotyping. Each 25 ml reaction contained 25 ng of genomic DNA, 1 £ PCR buffer (50 mM KCl, 20 mM Tris -HCl (pH 8.4)), 10 pmol of each primer, 2 mM MgCl 2 , 200 nM dNTP, 50 mM dATP and 1U Taq DNA polymerase (Amersham Pharmacia).…”
Section: Ssr Analysismentioning
confidence: 99%